2016
DOI: 10.4172/2155-9899.1000441
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Cytokine Receptors Involved in the Pathogenesis of Alzheimers Disease

Abstract: Inflammatory mechanisms are implicated in the pathology of Alzheimer’s disease (AD). However, it is unclear whether inflammatory alterations are a cause or consequence of neurodegeneration leading to dementia. Clarifying this issue would provide valuable insight into the early diagnosis and therapeutic management of AD. To address this, we compared the mRNA expression profiles of cytokines in the brains of AD patients with “non-demented individuals with AD pathology” and non-demented healthy control (ND) indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 189 publications
0
10
0
Order By: Relevance
“…In light of the fact that increased exchange of immunocytes may occur between peripheral lymphoid organs and the brain [135], it is noteworthy that the integrity of the BBB may not necessarily subsists in course of neurodegenerative disorders [136]. In fact, peripheral immunocytes have been indicated as factors that, when the inflammatory/immune equilibrium within the CNS is disrupted, are able to significantly influence progression of the AD brain pathology [74,137]. Now, considering the pleiotropic role of TRAIL in orchestrating key events of the inflammatory/immune response, it appears of interest how its immunoneutralization also leads to a rebalance of immunocytes ratios, with special regard to the Treg cell population either in the spleen and in the brain [18].…”
Section: The Impact Of Central and Peripheral Inflammatory/ Immune Rementioning
confidence: 99%
See 1 more Smart Citation
“…In light of the fact that increased exchange of immunocytes may occur between peripheral lymphoid organs and the brain [135], it is noteworthy that the integrity of the BBB may not necessarily subsists in course of neurodegenerative disorders [136]. In fact, peripheral immunocytes have been indicated as factors that, when the inflammatory/immune equilibrium within the CNS is disrupted, are able to significantly influence progression of the AD brain pathology [74,137]. Now, considering the pleiotropic role of TRAIL in orchestrating key events of the inflammatory/immune response, it appears of interest how its immunoneutralization also leads to a rebalance of immunocytes ratios, with special regard to the Treg cell population either in the spleen and in the brain [18].…”
Section: The Impact Of Central and Peripheral Inflammatory/ Immune Rementioning
confidence: 99%
“…In light of the fact that increased exchange of immunocytes may occur between peripheral lymphoid organs and the brain [ 135 ], it is noteworthy that the integrity of the BBB may not necessarily subsists in course of neurodegenerative disorders [ 136 ]. In fact, peripheral immunocytes have been indicated as factors that, when the inflammatory/immune equilibrium within the CNS is disrupted, are able to significantly influence progression of the AD brain pathology [ 74 , 137 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magaki et al ( 2007 ) showed that alteration in cytokines through peripheral blood mononuclear cells (PBMCs) might be detected early in mild cognitive impairment. Additionally, other studies have been done on the role of cytokines in AD, cognitive impairment, and neurological disorders (Aarli, 2005 ; Nagae and Araki, 2016 ). Chang et al ( 2012 ) discussed that p53 interacts with cellular factors, viral factors, and small RNAs, explaining its role in the development of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal neuronal injury is an important component of AD pathology and is closely related to the occurrence of neuritis, the deposition of Aβ and the hyperphosphorylation of tau proteins (27). A previous study into the causal relationship between neuroinflammation and AD reported that neuroinflammation may be involved in the pathogenesis of AD, and that an increase in the levels neuroinflammatory mediators was observed in AD (28). Thus, neuroinflammation serves an important role in the development of AD.…”
Section: Discussionmentioning
confidence: 99%